2019
DOI: 10.3390/w11020250
|View full text |Cite
|
Sign up to set email alerts
|

Orographic Effects of Geomorphology on Precipitation in a Pluvial Basin of the Eastern Tibetan Plateau

Abstract: The eastern Tibetan Plateau is subjected to strong spatial variations in precipitation, but the underlying reasons are still not well understood due to sparse in-situ meteorological observations. In this study, streamflow observations were adopted to investigate the orographic controls on precipitation in the Qingyijiang (QYJ) Basin of the eastern Tibetan Plateau. The method of multi-year annual water balance was used to estimate the basin-level precipitation using in-situ streamflow and flux-based evapotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The complex topography of the Korea, with many mountainous areas, has a significant impact on the spatial pattern of rainfall. Previous studies have highlighted the importance of orographic effects on the spatial distribution of rainfall in mountainous areas [1][2][3][4][5][6][7][8]. The mountain effect, also known as the orographic effect, may cause rainfall intensification, acting as a precursor of convective storm formation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The complex topography of the Korea, with many mountainous areas, has a significant impact on the spatial pattern of rainfall. Previous studies have highlighted the importance of orographic effects on the spatial distribution of rainfall in mountainous areas [1][2][3][4][5][6][7][8]. The mountain effect, also known as the orographic effect, may cause rainfall intensification, acting as a precursor of convective storm formation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that regions of higher elevations are more susceptible to global climate change than regions of lower elevations (Pepin et al 2015;Li et al 2020aLi et al , 2020bYou et al 2020); with increases in elevation, the annual mean temperature and precipitation generally become more variable (You et al 2020;Li et al 2020aLi et al , 2020cAguilar-Lome et al 2019;Minder et al 2018;Pepin et al 2015). Topography may affect climate through interference to lower atmospheric circulation and air-flow dynamics (Jiang 2003;Barros et al 2006;Yang and Zhang 2019;He et al 2019). Vegetation has been well recognized for playing a critical role in moderating warming effect via.…”
Section: Introductionmentioning
confidence: 99%